Quo Vadis SMK Pusat Keunggulan? - Anggun Apriyani; Masduki Asbari; Mayada Latifatu Zakiyah; Iin Nuraeny (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to find out the vocational high school system through cooperation with various parties. Ministry of Education and Culture. In this study report, he uses a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narration from the Youtube channel of the Indonesian Ministry of Education and Culture entitled